A rare case report of strangulated spigelian hernia mimicking an abdominal mass - SUNDAR, GEETA; Shetty, Sunil Kumar (Indian Journal of Case Reports, 2022)
A Spigelian hernia, an infrequent occurrence, is an abdominal wall hernia that occurs through the Spigelian fascia, an aponeurotic sheet located medially by rectus muscles and laterally by the semilunar line. The hernial sac lies either deep to the internal oblique muscles or between the oblique muscles. A Spigelian hernia requires repair due to the risk of incarceration with its relatively narrow neck. The below case report provide shows a patient, who came with an abdominal mass that was diagnosed as a strangulated Spigelian hernia and managed with an emergency surgery.